Improving Obstetric Provider Congenital Cytomegalovirus Knowledge and Practices - Megan H. Pesch; Carter Anderson; Erika Mowers (Hindawi Limited, 2020)
Background. Congenital cytomegalovirus infection (cCMV) is the most common congenital infection. Antenatal education is proven to reduce cCMV risk. Little is known about obstetric provider knowledge and practice patterns around cCMV. Objectives. To evaluate obstetric provider knowledge and practice patterns regarding cCMV at baseline and again after a brief educational intervention. Methods. Obstetric providers (N=53) at a US academic community hospital were invited to complete a survey regarding their knowledge and practice patterns around cCMV. Providers attended a brief presentation about cCMV and later were invited to repeat the same survey. Univariate statistics were calculated for baseline data, and prepost intervention comparison analyses were conducted. Results. Baseline cCMV knowledge was low at 49% (M=17.54 out of a possible 36, SD 6.4), with most providers (51%) reporting never counseling pregnant patients about cCMV. Post intervention, overall cCMV knowledge increased to 80% (M=29.33, SD 4.1, p<.001); provider intention to counsel about cCMV prevention increased to 100%. Conclusions. Obstetric provider knowledge about cCMV is low, which likely impacts their antenatal counseling. Educational initiatives to increase awareness about cCMV may increase antenatal education and thereby decrease the risk of cCMV.